Aspects of Legal Certainty of Land Declaration Letters as Guidelines for Land Registration with Negative Stelse - Chairunisa, Arrum; Gusti Ayu Ketut Rachmi Handayani, I; Karjoko, Lego (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Indonesia adheres to a negative publication system in land registration activities, where the state does not guarantee the correctness of the data presented in the certificate. This briefly illustrates the condition that legal certainty is not guaranteed in land registration activities. Many people still think that the land statement they own is proof of ownership of land rights. The results of the analysis show that basically the negative publication system adopted by Indonesia is not a publication system that does not guarantee legal certainty. This is because the negative publication system does not apply forever. The negative publication system in Indonesia still adheres to positive elements, where the government will guarantee the correctness of the data presented after 5 years of the land being registered. These restrictions actually aim to provide legal protection for land owners, so that it is possible to file lawsuits by parties who feel entitled. This can be seen in land cases in the judicial process, such as the case of decision Number 160/Pdt.G/2020/PN Plk, where the Judge stated that the Land Declaration Letter was valid and had binding legal force in the name of Mr. Baturung. Land Statement Letter Number: 140,594/300 /KL-MTG/PEM. This research uses normative research methods accompanied by primary legal materials and secondary legal materials. To answer legal issues by describing, examining, studying and explaining accurately and analyzing applicable laws and regulations as well as various legal expert opinions, with the aim of getting answers to the problems raised. The Land Declaration Letter is a letter issued by the sub-district.